Endotoxin Removal by Magnetic Separation‐Based Blood Purification. Issue 6 (6th December 2012) - Herrmann, Inge K.; Urner, Martin; Graf, Samuel; Schumacher, Christoph M.; Roth‐Z'graggen, Birgit; Hasler, Melanie; Stark, Wendelin J.; Beck‐Schimmer, Beatrice
Abstract This work describes a magnetic separation‐based approach using polymyxin B‐functionalized metal alloy nanomagnets for the rapid elimination of endotoxins from human blood in vitro and functional assays to evaluate the biological relevance of the blood purification process. Playing a central role in gram‐negative sepsis, bacteria‐derived endotoxins are attractive therapeutic targets. However, both direct endotoxin detection in and removal from protein‐rich fluids remains challenging. We present the synthesis and functionalization of ultra‐magnetic cobalt/iron alloy nanoparticles and a magnetic separation‐based approach using polymyxin B‐functionalized nanomagnets to remove endotoxin from human blood in vitro. Conventional chromogenic Limulus Amebocyte Lysate assays confirm decreased endotoxin activity in purified compared to untreated samples. Functional assays assessing key steps in host defense against bacteria show an attenuated inflammatory mediator expression from human primary endothelial cells in response to purified blood samples compared to untreated blood and less chemotactic activity. Exposing Escherichia coli‐positive blood samples to polymyxin B‐functionalized nanomagnets even impairs the ability of gram‐negative bacteria to form colony forming units, thus making magnetic separation based blood purification a promising new approach for future sepsis treatment.